Testing the efficiency of escape stairs in residential buildings in Sulaymaniyah city - Omed Juma Sedeeq; Hawar Taha Tawfiq (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
This paper studies the efficiency of escape stairs in multi-storey residential buildings as one of the most important means of evacuation in emergency cases. The study focused on the design aspects of escape routes, which is supposed to be considered during the designing process of the residential building, as a research problem that was not addressed in previous studies, especially the local ones. The aim of this research is to try test the performance of escape stairs in residential buildings in the city of Sulaimaniyah according to the international standards in construction of escape stairs in multi-storey residential buildings. The research assumes that residential buildings, even if they include a fire escape stairs designed based on design principles and standards, but still lack some essential details that clearly affect the performance of these stairs during emergencies. The study chose a number of multi-storey residential buildings in the city as a case study, which were examined using a (Check List) prepared for this purpose based on the international requirements and standards adopted in the design of escape stairs for residential buildings.The study concluded that the deficiencies in the design of these stairs were concentrated in the absence of major requirements confirmed by international standards, such as complete insulation of the residential floor, as well as the efficiency of the exit access, and the efficiency of egress routes.